(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Medicinal plants have historically served as significant reservoirs of therapeutic agents worldwide. India possesses an extensive repository of traditional medicinal flora, coupled with distinct plant and animal ecosystems. Contemporary advancements in comprehending the pathogenesis of peptic ulcers have propelled the pursuit of novel and enhanced drug therapies. In this particular investigation, the anti-ulcer potential of the seeds of Manilkara zapota, an indigenous medicinal plant, was rigorously assessed. Manilkara zapota seeds emanate from a deciduous tree within the Sapotaceae botanical family. These seeds were meticulously subjected to a comprehensive pharmacognostic evaluation. A multifaceted approach encompassing macroscopic, microscopic, physicochemical, and phytochemical methodologies was employed to discern defining characteristics for the identification and standardization of both the intact and pulverized forms of Manilkara zapota seed material. Such analytical endeavors served to effectively distinguish it from other botanical constituents.